Orthogonal perfect DFT Golay codes - Lanza-Gutierrez, J. M. (2017)
Deciding about which coding sequences should be used is an important issue in many communication systems, such as those employing Code Division Multiple Access (CDMA). In this paper, we propose a cascading electronic codec based on a recursive algorithm for the generation of perfect sequences, derived from an Inverse Discrete Fourier Transform (IDFT) of Golay codes. The sequences generated have a low Peak-to-Average Power Ratio (PAPR), around 3 dB, which is the PAPR of a sine wave. The proposal is compared to the original Golay codes, verifying that our codec provides better crosscorrelation and autocorrelation results, crucial to gain immunity to multi-path interference.